Pelaksanaan Pelayanan Publik Di Kantor Desa Karang Anyar Kecamatan Semendawai Timur - Ibrahim, Ibrahim; Niswah, Choirun; Efendi, Aris (Universitas Pendidikan Mandalika, 2024)
Abstract: This research is entitled